The effects of analytical and holistic reasoning perspective on innovation and business performance, a study of state own, FDI and private company in Vietnam - Mai Ngoc Khuong; Pham Dang Tuan; Nguyen Ngoc Duy Phuong (Cogent Business & Management)
This study examines the effects of analytical and holistic reasoning perspective on innovation and business performance in state owned, FDI, and private companies in Vietnam. The study was conducted on 382 companies. Data are analyzed through the use of partial least squares (PLS). The study results indicate that analytical and holistic reasoning perspective was a significant determinant of innovation and business performance. Furthermore, the analytical and holistic reasoning perspectivge impacted business performance both directly and indirectly. Thus, this study confirms the significance of an integrated approach to understanding the impacts of both direct and indirect effects of analytic and holistic reasoning perspectives on innovation and business performance in Vietnam. In addition, this study will contribute to the literature and in practice. It will help the policy maker to make good innovation and get high performance in the future. The limitations of the study will also be discussed.